Representasi Relasi Jender dalam Pemakaian Diksi pada Novel “Perempuan Berkalung Sorban” Karya Abidah El Khalieki - Suyanto Suyanto; Mujid F Amin (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2017)
This study aims to explain the use of diction which reflects gender relation in four aspects namely leniency, authority, mobility, and attitude. The material object of this research is Abidah El-Khalieki's novel Women to Wear headdress. Data collection using the method refer and note technique. Data analysis was used data reduction, data display, data verification, interpretation and theoretical meanings, and result conclusions. In the aspect of leniency shows the existence of allowances or the opportunity of women to indicate its existence in public spaces. Gender inequality is demonstrated by diction that States that in the wedding were not involved to define himself. Diction in the form of metaphor is dominated by metaphor symbolic stating that the woman just jewelry for her husband. Diction in attitude more widely used to describe the nature of stereotypes of women and gender bias. In general the diction in the novel more gender-equitable tend to PBS. Usage of diction are generally gender bias for comparison that finally found the gender-sensitive nature of the resolution. As for the use in the novel PBS dominated by symbolic figurative.